Polarization engineering of covalent triazine frameworks for highly efficient photosynthesis of hydrogen peroxide from molecular oxygen and water - Wu, Chongbei (2023)
Two-electron oxygen photoreduction to hydrogen peroxide (H2 O2 ) is seriously inhibited by its sluggish charge kinetics. Herein, a polarization engineering strategy is demonstrated by grafting (thio)urea functional groups onto covalent triazine frameworks (CTFs), giving rise to significantly promoted charge separation/transport and obviously enhanced proton transfer. The thiourea-functionalized CTF (Bpt-CTF) presents a substantial improvement in the photocatalytic H2 O2 production rate to 3268.1 µmol h-1 g-1 with no sacrificial agents or cocatalysts that is over an order of magnitude higher than unfunctionalized CTF (Dc-CTF), and a remarkable quantum efficiency of 8.6% at 400 nm. Mechanistic studies reveal the photocatalytic performance is attributed to the prominently enhanced two-electron oxygen reduction reaction by forming endoperoxide at the triazine unit and highly concentrated holes at the thiourea site. The generated O2 from water oxidation is subsequently consumed by the oxygen reduction reaction (ORR), thereby boosting overall reaction kinetics. The findings suggest a powerful functional-groups-mediated polarization engineering method for the development of highly efficient metal-free polymer-based photocatalysts.